Influence of glutathione-S-transferase (GST) inhibition on lung epithelial cell injury: role of oxidative stress and metabolism - Fletcher,ME; Boshier,PR; Wakabayashi,K; Keun,HC; Smolenski,RT; Kirkham,PA; Adcock,IM; Barton,PJ; Takata,M; Marczin,N (AMERICAN JOURNAL OF PHYSIOLOGY-LUNG CELLULAR AND MOLECULAR PHYSIOLOGY, 2015)
Oxidant-mediated tissue injury is key to the pathogenesis of acute lung injury. Glutathione-S-transferases (GSTs) are important detoxifying enzymes that catalyze the conjugation of glutathione with toxic oxidant compounds and are associated with acute and chronic inflammatory lung diseases. We hypothesized that attenuation of cellular GST enzymes would augment intracellular oxidative and metabolic stress and induce lung cell injury. Treatment of murine lung epithelial cells with GST inhibitors, ethacrynic acid (EA), and caffeic acid compromised lung epithelial cell viability in a concentration-dependent manner. These inhibitors also potentiated cell injury induced by hydrogen peroxide (H2O2), tert-butyl-hydroperoxide, and hypoxia and reoxygenation (HR). SiRNA-mediated attenuation of GST-π but not GST-μ expression reduced cell viability and significantly enhanced stress (H2O2/HR)-induced injury. GST inhibitors also induced intracellular oxidative stress (measured by dihydrorhodamine 123 and dichlorofluorescein fluorescence), caused alterations in overall intracellular redox status (as evidenced by NAD+/NADH ratios), and increased protein carbonyl formation. Furthermore, the antioxidant N-acetylcysteine completely prevented EA-induced oxidative stress and cytotoxicity. Whereas EA had no effect on mitochondrial energetics, it significantly altered cellular metabolic profile. To explore the physiological impact of these cellular events, we used an ex vivo mouse-isolated perfused lung model. Supplementation of perfusate with EA markedly affected lung mechanics and significantly increased lung permeability. The results of our combined genetic, pharmacological, and metabolic studies on multiple platforms suggest the importance of GST enzymes, specifically GST-π, in the cellular and whole lung response to acute oxidative and metabolic stress. These may have important clinical implications.